2007
DOI: 10.1002/mrdd.20139
|View full text |Cite
|
Sign up to set email alerts
|

Differential treatment intensity research: A missing link to creating optimally effective communication interventions

Abstract: Research over the past 50 years has yielded several promising approaches and many specific intervention techniques designed to enhance the communication and language development of young children with intellectual and developmental delays and disabilities. Yet virtually no systematic research has been conducted on the effects of different treatment intensities. We review how intervention intensity has been defined in the literature and propose a set of terms borrowed from medicine that are intended to capture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
477
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 497 publications
(491 citation statements)
references
References 37 publications
7
477
0
7
Order By: Relevance
“…On occasion, the clinician also modeled words that were child-specific and relevant to the conversation (e.g., prince, handsome). This approach is supported by reported association between individualized adult input in response to the child's initiations, and linguistic gains in children with communication disorders (see Camarata & Nelson, 2006;Hadley, Rispoli, Fitzgerald, & Bahnsen, 2011;Nelson et al, 1996;Warren, Fey, & Yoder, 2007).…”
Section: Interventionmentioning
confidence: 92%
“…On occasion, the clinician also modeled words that were child-specific and relevant to the conversation (e.g., prince, handsome). This approach is supported by reported association between individualized adult input in response to the child's initiations, and linguistic gains in children with communication disorders (see Camarata & Nelson, 2006;Hadley, Rispoli, Fitzgerald, & Bahnsen, 2011;Nelson et al, 1996;Warren, Fey, & Yoder, 2007).…”
Section: Interventionmentioning
confidence: 92%
“…In Table 1, we provide an overview of treatment intensity dimensions from three selected theoretical papers (Barnett et al 2004;Mellard et al 2010;Warren et al 2007). Seventeen dimensions were generated across studies with overlap found for only five aspects of intensity including treatment session length (minutes), treatment session frequency (per day/week), total treatment duration (weeks), number of practice opportunities supported by the treatment, and interventionist characteristics.…”
Section: Defining Treatment Intensitymentioning
confidence: 99%
“…Although dose was described across all three papers as session length and frequency and across two papers as total treatment duration, other aspects of dose were also considered important. Warren et al (2007) described the necessity of accounting for the number of teaching episodes accurately provided per treatment session as well as cumulative intensity (i.e., the product of all other dose variables). These authors suggested that various combinations of dose may be differentially important according to interventions, contexts, and student Barnett et al (2004) describe the idea of ''engineering productive practice opportunities'' (p. 574).…”
Section: Defining Treatment Intensitymentioning
confidence: 99%
See 2 more Smart Citations